Hydration in soccer: a review - Ralo Monteiro, C.; Guerra, I.; Leite de Barros, T. (Revista Brasileira de Medicina do Esporte, 2003)
Soccer is a sport of very particular features regarding hydration, particularly as it does not have regular breaks for players to drink fluids during matches. Fluid intake during exercise is quite beneficial for players, as it minimizes dehydration effects. Dehydration may cause performance to decrease. To prevent that from taking place, players must be educated as to the importance of fluid intake before, during and after the practice of exercises.